Endothelium-independent vasorelaxation effects of 16-O-acetyldihydroisosteviol on isolated rat thoracic aorta - Pantan,R. (Elsevier Inc., 2015)
© 2014 Elsevier Inc. All rights reserved. Aims: The aim of this study is to investigate the vasorelaxant effect of 16-O-acetyldihydroisosteviol (ADIS) and its underlying mechanisms in isolated rat aorta. Main methods: Rat aortic rings were isolated, suspended in organ baths containing Kreb's solution, maintained at 37°C, and mounted on tungsten wire and continuously bubbled with a mixture of 95% O2 and 5% CO2 under a resting tension of 1 g. The vasorelaxant effects of ADIS were investigated by means of isometric tension recording experiment. Key findings: ADIS (0.1 μM-3 mM) induced relaxation of aortic rings pre-contracted by phenylephrine (PE, 10 μM) and KCl (80 mM) with intact-endothelium (Emax = 79.26 ± 3.74 and 79.88 ± 3.79, respectively) or denuded-endothelium (Emax = 88.05 ± 3.69 and 78.22 ± 6.86, respectively). In depolarization Ca2+-free solution, ADIS inhibits calcium chloride (CaCl2)-induced contraction in endothelium-denuded rings in a concentration-dependent manner. In addition, ADIS attenuates transient contractions in Ca2+-free medium containing EGTA (1 mM) induced by PE (10 μM) and caffeine (20 mM). By contrast, relaxation was not affected by tetraethylammonium (TEA, 5 mM), 4-aminopyridine (4-AP, 1 mM), glibenclamide (10 μM), barium chloride (BaCl2, 1 mM), and 1H-[1,2,3]oxadiazolo[4,3-α]quinoxalin-1-one (ODQ, 1 μM). Significance: These findings reveal the vasorelaxant effect of ADIS, through endothelium-independent pathway. It acts as a Ca2 + channel blocker through both intracellular and extracellular Ca2 + release.